The art of architecture wayfinding: navigating by objects, boundaries, and time - Agung Dwiyanto; Arnis Rochma Harani; Intan Bisyarah; Fariz Hirzan (Journal of Architecture and Urbanism, 2025)
The purpose of this paper is to explore various forms of wayfinding through spatial reading. In particular, this article emphasizes how hidden clues play an important role in human movement and the wayfinding process. The purpose of this paper is to highlight hidden clues that are crucial to understanding architectural spatiality as a process of wayfinding. A film that contains a wayfinding narrative will be dismantled in this paper to explore various the arts of wayfinding. The selection of the films was based on the possibility of spatial reading, especially those that reflect the story of human movement and the wayfinding process. The analysis is based on observations of the film, particularly how spatial settings are compiled and used to wayfinding clues as the observed data. The data was collected by observing the actors about their wayfinding strategies. Using catalogs and diagrams, the results of the data were analyzed to obtain a spatial picture of wayfindings. Three aspects of hidden clues determine a person‘s wayfinding, namely objects, boundaries, and time. In terms of wayfinding, these three aspects may be considered outside of the physical form of architectural space. The results of the study contribute to the development of an architectural wayfinding system based on spatial narratives.